Minimum Wage Noncompliance and the Employment Decision - Yaniv, Gideon (Journal of Labor Economics, 2001)
The employment effects of minimum wage noncompliance have been the focus of several theoretical contributions to the minimum wage literature, the dominating conclusion being that the noncomplying employer, while reducing employment below the free‐market level, will still employ more labor than he would if complying. Allowing, however, for partial compliance, this study applies a portfolio‐choice approach to the employer’s problem, concluding surprisingly that the minimum wage law may give rise to a full‐compliance employment effect even if it is partially evaded. This result is further shown to hold with regard to labor market laws in general.